In the Absence of Central pre-B Cell Receptor Selection, Peripheral Selection Attempts to Optimize the Antibody Repertoire by Enriching for CDR-H3 Y101 - Khass, Mohamed; Blackburn, Tessa; Elgavish, Ada; Burrows, Peter D.; Schroeder, Harry W. (Frontiers in Immunology, 2018)
Sequential developmental checkpoints are used to ‘optimize’ the B cell antigen receptor repertoire by minimizing production of autoreactive or useless immunoglobulins and enriching for potentially protective antibodies. The first and apparently most impactful checkpoint requires µHC to form a functional preBCR by associating with surrogate light chain, which is composed of VpreB and λ5. Absence of any of the preBCR components causes a block in B cell development that is characterized by severe immature B cell lymphopenia. Previously, we showed that preBCR controls the amino acid content of the third complementary determining region of µHC (CDR-H3) by using a VpreB amino acid motif (RDR) to select for tyrosine at CDR-H3 position 101 (Y101). In antibodies bound to antigen, Y101 is commonly in direct contact with the antigen, thus preBCR selection impacts the antigen binding characteristics of the repertoire. In this work, we sought to determine the forces that shape the peripheral B cell repertoire when it is denied preBCR selection. Using BrdU incorporation and evaluation of apoptosis; we found that in the absence of preBCR there is increased turnover of B cells due to increased apoptosis. CDR-H3 sequencing revealed that this is accompanied by adjustments to DH identity, DH reading frame (RF), JH, and CDR-H3 amino acid content. These adjustments in the periphery led to wild type levels of CDR-H3 Y101 content among transitional (T1), mature recirculating, and marginal zone (MZ) B cells. However, peripheral selection proved incomplete, with failure to restore Y101 levels in follicular B cells and increased production of dsDNA binding IgM antibodies.